Dyslexia associated gene KIAA0319 regulates cell cycle during human neuroepithelial cell development - Paniagua, Steven; Cakir, Bilal; Hu, Yue; Kiral, Ferdi Ridvan; Tanaka, Yoshiaki; Xiang, Yangfei; Patterson, Benjamin; Gruen, Jeffrey R.; Park, In-Hyun (Frontiers in Cell and Developmental Biology, 2022)
Dyslexia, also known as reading disability, is defined as difficulty processing written language in individuals with normal intellectual capacity and educational opportunity. The prevalence of dyslexia is between 5% and 17%, and the heritability ranges from 44% to 75%. Genetic linkage analysis and association studies have identified several genes and regulatory elements linked to dyslexia and reading ability. However, their functions and molecular mechanisms are not well understood. Prominent among these is KIAA0319, encoded in the DYX2 locus of human chromosome 6p22. Association of KIAA0319 with reading performance has been replicated in independent studies and in different languages. Rodent models suggest that kiaa0319 is involved in neuronal migration, but its precise function is unknown. We hypothesize that the clinical association of KIAA0319 with reading performance and dyslexia is a consequence of altered function during neurogenesis in the early stages of embryonic brain development. To test this hypothesis, we used a human embryonic stem cell (hESC) model of cortical neural differentiation to probe the function of KIAA0319 in neurogenesis. We knocked down KIAA0319 expression in hESCs and induced neuroectodermal differentiation to measure the effects on transitions through stages of typical neuronal development. We found that KIAA0319 is essential for neuroepithelial cell differentiation, which could affect radial migration as well as downstream differentiation into diverse populations of brain cells. These results suggest a mechanism whereby KIAA0319 could influence complex traits such as reading.